PENGEMBANGAN DAN PENINGKATAN MINAT BACA ANAK SEBAGAI UPAYA PENGALIHAN GADGET DI DESA SUMOKALI - Dina Merris Maya Sari (STKIP PGRI Sidoarjo, 2018)
Gadget is a familiar technology for primary school-aged children. The use of gadgets in primary school-aged children makes them feel lazy and less interest to read. Reduced interest in reading in primary school-aged children affects the learning achievement in school. The purpose of this activity is to develop interest in reading in primary school-aged children as an effort to divert and reduce the use of gadgets in children. The method used is design assistance with Participatory Action Research, which includes a series of stages of participation, action and research. From various stages, parents are invited and taught to take an active role in assisting and stimulating reading interest in children. This stage is also filled with time agreement in using gadgets as well as reading a book with parental assistance. With the existence of several stages, parents and children look active and happy in carrying out activities development of reading interest in children. Children began to decrease in the use of gadgets as well as interest in reading improved.